Implementation of Education-Based Religious Moderation Through the Culture of Tolerance Festival for Elementary School Students in Kutambaru Village, Karo Regency - Fadil Hsb, Ahmad; Rahmi, Najwa Ulfi; Siregar, Fitri Holila; Atika, Atika (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of religious moderation through the Cultural Tolerance Festival organized by KKN UINSU 83 students in Kutambaru Village, Tiganderket District, Karo Regency. The research uses a qualitative descriptive method with an exploratory approach to understand the process, types of activities, and participant involvement during the festival. Data collection was carried out through participatory observation, documentation of activities, and relevant literature studies. The obtained data were analyzed thematically through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the poetry competition encouraged courage to express and internalize the value of tolerance through literary texts, while the solo vocal competition strengthened self-confidence and togetherness across participant backgrounds. The quiz competition contributed to increased knowledge, teamwork, and sportsmanship, while the coloring competition fostered creativity, imagination, and a joyful atmosphere. Overall, this festival created harmonious interactions involving children, teachers, parents, and the community as a concrete practice of religious moderation. These findings confirm that an arts and culture-based cultural-educational approach is effective in instilling the value of tolerance from an early age and can be a relevant model of community service to be applied in other multicultural areas.